Urgensi Pembinaan Moral Dalam Pembentukan Karakter Siswa di SMP Negeri 3 Palopo - Rika; Hasbi; Amir Faqihuddin Assafari (Indonesian Journal of Islamic Educational Review, 2024)
This article discusses the urgency of moral development in forming the character of students at SMP Negeri 3 Palopo. This research aims to: (1) determine the character formation of students at SMP Negeri 3 Palopo; (2) knowing the obstacles faced by Pai teachers in forming the character of students at SMP Negeri 3 Palopo; (3) find out solutions to overcome obstacles for Islamic religious education teachers in forming student character at SMP Negeri 3 Palopo. This type of research is qualitative using psychological, pedagogical and sociological approaches, data sources obtained through observation, interviews, documentation. This research data is analyzed through data reduction, data presentation and drawing conclusions. The results of this research show that character formation at SMP Negeri 3 Palopo has been taking place in accordance with the provisions and norms of education in the form of honest character, good manners and discipline. The obstacles faced by Islamic religious education teachers at SMP Negeri 3 Palopo are the student environment and friends. peers, and school environment. The solution to these obstacles is by involving parents and families and providing guidance and counseling for students and providing a reward and motivation system and involving the entire school environment in character formation.